Extrasynaptic therapeutic targets in substance use and stress disorders. (January 2022) - Hodebourg, Ritchy; Kalivas, Peter W.; Kruyer, Anna
Abstract : Treatments for substance use and stress disorders are based on ameliorating behavioral symptoms, not on reversing the synaptic pathology that has the potential to cure disorders. This failing arises in part from a research focus on how pre- and postsynaptic physiology is changed even though key neuropathology exists in the perisynaptic neuropil that homeostatically regulates synaptic transmission. We explore recent findings from the substance use and stress disorder literature pointing to a key role for perisynaptic astroglia and signaling in the extracellular matrix (ECM) in regulating synaptic pathology. We conclude that drugs and stress initiate long-lasting changes in brain synapses via enduring neuroadaptations in astroglia and the ECM, and that modulating extrasynaptic regulators may be therapeutically useful. Highlights: Animal models of substance use and stress disorders arise from overlapping enduring changes in synaptic plasticity produced by drug use or stress exposure. Non-neuronal components of the synapse, including astroglia and the extracellular matrix establish and sustain maladaptive synaptic plasticity. Synaptic proximity of astroglial processes is altered by environmental stress and addictive drug use, conferring relapse-vulnerability. Catalytic signaling in the extracellular matrix is necessary for conditioned drug seeking and stress responding. Regulating astroglial plasticity and extracellular matrix signaling highlights novel molecular targets for treating addictive drug use and stress disorders.